A comparison study of the top five journals on Human Resource Management indexed with Scopus - Janen, T. (University of Jaffna, 2020)
This paper presents the quantitative comparison of the top five journals based on many articles published on Human Resource Management (HRM) indexed with Scopus. A total of 102,333 contributions were published in 10,186 Human Resource Management journals. Scopus is one of the large abstract and citation databases of peer-reviewed literature. It has comprehensive metrics to evaluate the journal quality from over 5,000 publishers. This study selected the top five journals publishing human resource management related research output. The top five journals were selected concerning number of articles published by respective journals on human resource management. Quality indicators number of articles published on HRM and h index, CiteScore publication by year, SCI mago journal rank by year, Source Normalized impact/year, source citation by year, source documents by year, percentage of document not cited by year, and international collaboration were used to compare the journal performance. The sum of the research output in the Human resource management journal shows high citation throughout the period considered, it is a potential journal in the field of HRM and trend of international author contribution. The output of this study will help the academics, researchers and information professionals select the quality and potential journals in the field of HRM to publish their research and subscribe to the library.
Keywords: citescore; human resource management; journal performance indicators; scimago journal ranking